Passive acoustic monitoring off Vancouver Island reveals extensive use by at-risk Resident killer whale (Orcinus orca) populations - Riera, A; Pilkington, JF; Ford, JKB; Stredulinsky, EH; Chapman, NR (Endangered Species Research, 2019)
Two sympatric populations of fish-eating Resident killer whales inhabit the coastal waters of British Columbia, Canada: Southern and Northern Resident killer whales. These populations are listed under Canada’s Species at Risk Act (SARA) as ‘endangered’ and ‘threatened’, respectively. Relatively little is known about their habitat use outside of the sheltered waters along the east coast of Vancouver Island, especially during the winter. SARA requires the identification of critical habitat for these populations. High densities of Chinook salmon—their primary prey—are found around Swiftsure Bank, an area identified as potential critical habitat for Southern Residents. However, it is a difficult area to survey for whales using conventional small-boat approaches. Here, we used 2 yr of data collected from an autonomous acoustic recorder deployed at Swiftsure Bank from 2009-2011 to assess the year-round habitat use of this area by Resident killer whales. Overall, Resident killer whales were detected on 244 of 680 monitored days (36%). Southern Residents were heard in all months, with activity peaking during the summer. Northern Residents were also heard throughout the year, but were mostly detected in the spring and fall, which indicates the 2 populations may differ in their strategies for using this common foraging area. High levels of use by both of these populations highlights the importance of Swiftsure Bank to both, supporting the expansion of Resident killer whale critical habitat to include this site.